Pengembangan Media Sex Education Book Untuk Meningkatkan Pemahaman Pendidikan Seksual Pada Anak Usia Dini - Nur Nurbaiti; Aip Saripudin; Masdudi Masdudi (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2022)
ABSTRACTThe understanding of sexual education for children aged 5-6 years at RA Nur Kamal has not developed optimally, besides that the media related to sexual education is still limited in its availability. This study aims to develop sexual education using the Sex Education Book media in order to increase the understanding of sexual education for children aged 5-6 years in RA. This study uses the Research and Development method by using data collection techniques in the form of observation, interviews, questionnaires and documentation. The data analysis technique used is descriptive qualitative and descriptive quantitative. The results of this study are a media Sex Education Book that has been declared